Sustainable Production in Food and Agriculture Engineering - Krolczyk, Jolanta B.; Sobczak, Pawel; Zukiewicz-Sobczak, Wioletta (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is a collection of original research and review papers that report on the state of the art and recent advancements in food and agriculture engineering, such as sustainable production and food technology. Encompassed within are applications in food and agriculture engineering, biosystem engineering, plant and animal production engineering, food and agricultural processing engineering, storing industry, economics and production management and agricultural farms management, agricultural machines and devices, and IT for agricultural engineering and ergonomics in agriculture.